2018
DOI: 10.7554/elife.38740
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor pathway controlling stopping behavior during chemotaxis in the Drosophila melanogaster larva

Abstract: Sensory navigation results from coordinated transitions between distinct behavioral programs. During chemotaxis in the Drosophila melanogaster larva, the detection of positive odor gradients extends runs while negative gradients promote stops and turns. This algorithm represents a foundation for the control of sensory navigation across phyla. In the present work, we identified an olfactory descending neuron, PDM-DN, which plays a pivotal role in the organization of stops and turns in response to the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 113 publications
4
79
0
Order By: Relevance
“…Once Figure 2Diii). This result is consistent with the behavior of wild-type larvae in response to attractive odors (33). It establishes that PiVR can automatically detect and accurately track animal in real time.…”
Section: Benchmarking Pivr Performances By Eliciting Larval Chemotaxisupporting
confidence: 84%
See 1 more Smart Citation
“…Once Figure 2Diii). This result is consistent with the behavior of wild-type larvae in response to attractive odors (33). It establishes that PiVR can automatically detect and accurately track animal in real time.…”
Section: Benchmarking Pivr Performances By Eliciting Larval Chemotaxisupporting
confidence: 84%
“…For all experimental conditions, we found that the turn-triggered average of the sensory experience showed a decrease in stimulus intensity for several seconds preceding a stop (17,56,61) (Figure 5E). This characteristic decrease in stimulus has been shown to inhibit the activity of the olfactory sensory neurons, which in turn enhances the probability of interrupting forward peristalsis (17,33).…”
Section: Defining the Nature Of Taste-driven Responses In Adult Fliesmentioning
confidence: 99%
“…There is evidence that the transcription factor FoxP plays a role in valuebased decision making, implicating these mutants as possible targets for future studies [55]. Finally, encounter-elicited stopping might be unique to walking Drosophila and larvae [56], since remaining stationary is more difficult in flight. Still, the reflexive counterturns that flying Drosophila execute after losing a plume [19] do bear loose resemblance to the increased stop rates following a drop in encounter frequency, so these decisions may have a common origin, but a different behavioral response.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we were able to overcome these obstacles by using the tractable genetic model system of Drosophila melanogaster larva. In this system, we could combine: i) large-scale electron microscopy reconstruction of neural circuits due to the relatively small size of its brain (Jovanic et al, 2016;Ohyama et al, 2015); ii) targeted manipulation of uniquely identified neuron types (Jovanic et al, 2016;Ohyama et al, 2015;Tastekin et al, 2018), iii) and functional imaging of neural activity.…”
Section: Introductionmentioning
confidence: 99%